Синтез та діуретична дія 8-амінозаміщених 7-(2-гідрокси-3-п-метоксифеноксипропіл-1)-3-метилксантину - Ivanchenko, D. H.; Romanenko, M. I.; Aleksandrova, K. V.; Samura, B. A.; Duchenko, K. A.; Sinchenko, D. N. (National University of Pharmacy, 2017)
It has been found that natural xanthines, as well as their synthetic analogs, possess the diuretic effect. Analysis of the literature proves that there is a great opportunity of applying synthetic derivatives of N-methylated xanthines as potential diuretics.Aim. To develop preparative methods of the synthesis of 8-aminosubstituted of 7-(2-hydroxy-3-p-metoxyphenoxypropyl-1)-3-methylxanthine and study their physical, chemical and biological properties. Results. The synthesis of a series of 8-aminosubstituted of 7-(2-hydroxy-3-p-metoxyphenoxypropyl-1)-3-methylxanthine was carried out. According to the results of the biological testing the compounds synthesized belong to the toxicity of class IV. 7-(2-Hydroxy-3-p-methoxyphenoxypropyl-1)-8-(furyl-2-methylamino)-3-methylxanthine xanthine shows the highest diuretic activity, and hence, requires a more in-depth study since it is twice more active than hydrochlorothiazide. It should be emphasized that all compounds synthesized exhibit a marked diuretic effect. Experimental part. 8-Bromo-7-(2-hydroxy-3-p-methoxyphenoxypropyl-1)-3-methylxanthine was obtained by heating 8-bromo-3-methylxanthine with p-methoxyphenoxymethyloxirane in butanol-1 and in the presence of N,N-dimethylbenzylamine. 8-Aminosubstitutied of 7-(2-hydroxy-3-p-metoxyphenoxypropyl-1)-3-methylxanthine was obtained by boiling of bromoalcohol with the primary and secondary amines. The structure of the compounds synthesized was unambiguously confirmed by NMR-spectroscopy. The acute toxicity of the compounds obtained was studied by Kerber method. The study of the diuretic activity of the compounds was carried out using Ye. Berkhin method. Hydrochlorothiazide was used as a reference substance. Conclusions. Simple methods for the synthesis of 8-amino-7- (2-hydroxy-3-p-methoxyphenoxypropyl-1)-3-methylxanthines have been developed. The structure of the compounds synthesized has been confirmed by the method of NMR 1H-spectroscopy. The acute toxicity and the diuretic activity of the compounds obtained have been studied.